A solanum beetle on a fabaceous weed: Host plant generalization and specialization are two sides of the same coin. Issue 1 (3rd March 2017) - Ueno, Hideki; Fujiyama, Naoyuki; Kahono, Sih; Hartini, Sri; de Jong, Peter W.; Katakura, Haruo
Abstract: Investigations of the ongoing evolutionary change of host specificity, especially of that in the initial phase, contribute largely to our understanding of the mechanisms responsible for the diversification of phytophagous insects. However, empirical studies of this aspect in natural systems are very scanty. In the present study, we document the evolutionary change of the degree of adaptation to an introduced legume centro by adults and larvae of the herbivorous ladybird beetle Henosepilachna vigintioctopunctata (Fabricius), which depends normally on various solanaceous plants. Results obtained through experiments conducted in seven successive years revealed a fluctuating degree of adaptation, but with a gradual increase, to centro by H. vigintioctopunctata, showing a tendency towards host plant generalization. Of particular importance, our results suggest that both host plant specialization and generalization are possible evolutionary outcomes of a dynamic initial phase of ongoing host range expansion. In addition, results of quantitative genetic analyses on larval development and other circumstantial evidence suggested that the evolutionary trajectories to specialization/generalization are largely determined by ecological conditions rather than by the insects' intrinsic genetic architecture. We also discuss some special aspects of acquisition of, and adaptation to, novel hosts by H. vigintioctopunctata and other herbivorous beetles, of which adults also feed on plant leaves. Abstract : We document the evolutionary change of the degree of adaptation to the introduced legume Centrosema molle by adults and larvae of the herbivorous ladybird beetle Henosepilachna vigintioctopunctata, which depends normally on various solanaceous plants. Results obtained through experiments conducted in seven successive years revealed a fluctuating degree of adaptation, but with a gradual increase, to centro by H. vigintioctopunctata, showing a tendency toward host plant generalization. Of particular importance, our results suggest that both host plant specialization and generalization are possible evolutionary outcomes of a dynamic initial phase of ongoing host range expansion.